The effect of composition MnFe2O4 / PANi nanocomposite on the microstructure that synthesized by spin coating method - Lucya Sinurat; Yenni Darvina; - Ramli; - Ratnawulan (Department of Physics – Universitas Negeri Padang UNP, 2020)
Manganese ferrite has the structure of MnFe2O4 which in the process of making it uses manganese mineral powder. Based on the MnFe2O4 testing is one material that is suitable for use as a composite by mixing other binders in it. Polyaniline (PANi) is a polymer that can be used as a binding material which is an attractive conductive polymer because it has unique properties and good thermal stability. This research was conducted by making three variations of the composition of MnFe2O4 / PANi namely 40%: 60%, 50%: 50%, and 60%: 40% made using the spin coating method. This research was conducted to investigate the effect of composition on the microstructure of the MnFe2O4 / PANi nanocomposite layer using the spin coating method. The microstructure to be investigated is the functional group of grain size and thickness of the nanocomposite layer. The tools used in this study are Fourier Transform Infrared (FTIR) used to obtain the functional groups of nanocomposite layers, X-ray Diffraction (XRD) is used to get the size of crystals and microstructure of crystals, and the Scanning Electron Microscope (SEM). Characterization and Scanning Electron Microscope (SEM) are used to obtain grain size and thickness of the nanocomposite layer. The results of the FTIR characterization are the functional groups of MnFe2O4 / PANi which produce absorption bands at wavenumbers 3214.85 cm-1, 3353.86 cm-1, and 3214.03 cm-1, which are O-H groups. The absorption band at wavenumbers 717.00 cm-1, 763.94 cm-1, and 747.31 cm-1 is the C-H group showing PANi. Absorption peaks that are below 1000 cm-1 that is at wavenumbers 874.78 cm-1, 924.18 cm-1, and 895.96 cm-1 show indications of Manganese Ferrit. The results of the XRD characterization were crystal size and microstrain, each of which had a crystal size composition of 49.90478417 nm, 45.29656118 nm, and 44.52213202, and then for the value of the microstrain, each variation was 0.116667149, 0.15983276, and 0.183718732. Then from SEM characterization results obtained grain size values of 0.445 μm, 0.426 μm, 0.318 μm, while the thickness obtained for each variation is 1.29 μm, 2.02 μm, and 2.20 μm. Based on the results of the study, the greater the addition of PANi composition given, the value of crystal size, grain size also increases while the value of microstructure and thickness decreases.